Modifying genetic epilepsies – Results from studies on tuberous sclerosis complex. (April 2020) - Jozwiak, Sergiusz; Kotulska, Katarzyna; Wong, Michael; Bebin, Martina
Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant neurocutaneous disorder affecting approximately 1 in 6, 000 in general population and represents one of the most common genetic causes of epilepsy. Epilepsy affects 90% of the patients and appears in the first 2 years of life in the majority of them. Early onset of epilepsy in the first year of life is associated with high risk of cognitive decline and neuropsychiatric problems including autism. Recently TSC has been recognized as a model of genetic epilepsies. TSC is a genetic condition with known dysregulated mTOR pathway and is increasingly viewed as a model for human epileptogenesis. Moreover, TSC is characterized by a hyperactivation of mTOR (mammalian target of rapamycin) pathway, and mTOR activation was showed to be implicated in epileptogenesis in many animal models and human epilepsies. Recently published studies documented positive effect of preventive or disease modifying treatment of epilepsy in infants with high risk of epilepsy with significantly lower incidence of epilepsy and better cognitive outcome. Further studies on preventive treatment of epilepsy in other genetic epilepsies of early childhood are considered. This article is part of the special issue entitled 'New Epilepsy Therapies for the 21st Century – From Antiseizure Drugs to Prevention, Modification and Cure of Epilepsy'. Highlights: Epileptogenesis may be modified in animal models and patients. Prevention of epilepsy is particularly feasible in tuberous sclerosis complex. Clinical trials in TSC patients suggest vigabatrin may have antiepileptogenic effects. TSC mouse models indicate mTOR inhibitors have strong antiepileptogenic potential.